PERAN ORANG TUA DALAM PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA DINI - Lestari, Maghfirotul Firmaning (Ibtida'iy : Jurnal Prodi PGMI, 2024)
The aim of this research is to examine the role of parents in the socio-emotional formation of early childhood. Early childhood is often called the golden age, meaning that this age will determine what students' development will be like in the future. Discussing this, parents are the closest people to children, so of course it can be said that children's development reflects the parenting style provided by their parents. The method used in this research is qualitative research with a literature review method by summarizing the results of studies that are relevant to the research topic using the traditional review method. The results of this research are the role of parents in shaping children's social and emotional character. Parental anxiety and self-esteem can influence a child's personality. Parents must pay attention to this to form good children. Education provided by parents and the surrounding environment is important for developing children's potential, especially socially and emotionally. Parents become educators, caregivers, motivators and examples, forming children's values towards the environment. Parents and teachers need to build interaction and communication with children so that children can manage their emotions well. Children should be educated in a positive environment for a positive attitude. Every child is unique, the role of parents and teachers is important to direct and guide children in managing emotions. Parents play a significant role in forming the social and emotional character of early childhood, determining positive or negative child development based on the education provided.